Analysis of gastric and duodenal biopsy results in patients presenting with dyspepsia: a cross-sectional study in a middle eastern population - Mohammed Hussein Kamareddine; Youssef Ghosn; Naseem Bou-Ayash; Said Farhat; Antonios Tawk; Haneen Bou-Ayash; Nader Mokamer; Rawad Yared; Mouna Aoun; Salem Khoury; George Cortas; Gide Jabbour; et al. (BMJ Open Gastroenterology)
Objective Correa’s cascade is a ‘Model for Gastric Cancer Development’ described by Peleyo Correa. The reversibility of Correa’s cascade remains debatable. The literature contains insufficient data on the specific stage of the cascade during which Helicobacter pylori is detected, treated, and the effect on prognosis. Herein, we aim to determine the prevalence of various precancerous and cancerous gastric lesions in patients presenting with dyspepsia, the prevalence of gastritis and H. pylori infection, the prevalence of duodenal pathology in patients presenting with dyspepsia, identify the stage of H. pylori detection in relation to Correa’s cascade, and investigate a possible relationship between H. pylori and celiac disease.Design Retrospective cross-sectional study conducted on a middle eastern population at a Lebanese tertiary hospital centre. 1428 patients presenting with dyspepsia underwent gastroscopy with gastric and duodenal biopsies. Variables include age, sex, presence/absence of H. pylori infection, and histopathological analysis of gastric and duodenal biopsies.Results Being above 40 years of age was associated with increased likelihood of exhibiting abnormal gastric biopsy result. Gastritis and metaplasia were detected more frequently than glandular atrophy (p<0.001) with gastritis being present the most (p<0.001). The presence of H. pylori and the gastric biopsy results were not associated with any of the duodenal biopsy results.Conclusion The burden of H. pylori infection in patients with dyspepsia was high. H. pylori was detected at various precancerous lesions with varying significance. The prevalence of duodenal adenocarcinoma in dyspeptic patients is unexpectedly high. No association between gastric and duodenal pathologies was found.